Author Correction: The sugar substitute Stevia shortens the lifespan of Aedes aegypti potentially by N-linked protein glycosylation - Arvind Sharma (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.